A multifunctional drug combination shows highly potent therapeutic efficacy against human cancer xenografts in athymic mice. - Xiu-Jun Liu; Yan-Bo Zheng; Yi Li; Shu-Ying Wu; Yong-Su Zhen (PLoS ONE)
The tumor microenvironment plays a crucial role during tumor development. Integrated combination of drugs that target tumor microenvironment is a promising approach to anticancer therapy. Here, we report a multifunctional combination of low-cytotoxic drugs composed of dipyridamole, bestatin and dexamethasone (DBDx) which mainly acts on the tumor microenvironment shows highly potent antitumor efficacy in vivo. In mouse hepatoma H22 model, the triple drug combination showed synergistic and highly potent antitumor efficacy. The combination indices of various combinations of the triple drugs were between 0.2 and 0.5. DBDx inhibited the growth of a panel of human tumor xenografts and showed no obvious systemic toxicity. At tolerated doses, DBDx suppressed the growth of human hepatocellular carcinoma BEL-7402, HepG2, and lung adenocarcinoma A549 xenografts by 94.5%, 93.7% and 96.9%, respectively. Clonogenic assay demonstrated that DBDx showed weak cytotoxicity. Western blot showed that Flk1 and Nos3 were down-regulated in the DBDx-treated group. Proteomic analysis showed that DBDx mainly affected the metabolic process and immune system process; in addition, the angiogenesis and VEGF signaling pathway were also affected. Conclusively, DBDx, a multifunctional drug combination of three low-cytotoxic drugs, shows synergistic and highly potent antitumor efficacy evidently mediated by the modulation of tumor microenvironment. Based on its low-cytotoxic attributes and its broad-spectrum antitumor therapeutic efficacy, this multifunctional combination might be useful in the treatment of cancers, especially those refractory to conventional chemotherapeutics.